Spectral representation for generalized operator-valued Toeplitz kernels - Chernobai, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove an integral representation for operator-valued Toeplitz kernels. The proof is based on the spectral theory of the corresponding differential operator constructed from this kernel and acting in a Hilbert space.